Thromboembolic risk of movable type left atrial appendage thrombi in patients with atrial fibrillation under widespread use of anticoagulants. (14th October 2021) - Mine, T; Sugitami, M; Fukuhara, E; Kitagaki, R; Ishihara, M
Abstract: Background: Left atrial appendage thrombi (LAAT), especially movable type LAAT, have been reported to be high-risk for thromboembolic events in patients with atrial fibrillation (AF). However, thromboembolic risk of the movable-type LAAT under widespread use of anticoagulant therapy remains unclear. Methods: We retrospectively studied 65 LAAT patients taking anticoagulants out of 1381 consecutive patients who underwent transthoracic echocardiography prior to cardioversion or catheter ablation for AF. Patients with significant valvular disease and coagulation disorder were excluded. Clinical data were evaluated at the time of TEE. The LAAT were classified into movable and fixed type LAAT by three independent observers. Results: Sixteen of 65 LAAT patients showed movable type LAAT. During follow-up (42±34 months), one patient underwent emergency thrombectomy, 5 patients developed thromboembolic event, and 12 patients died. There were no differences in clinical data, parameters, thrombectomy/thromboembolic event, and survival rate between patients with movable and fixed type LAAT. Conclusion: Thromboembolic risk of the movable-type LAAT is the same as fixed type LAAT, under widespread use of anticoagulant therapy. Funding Acknowledgement: Type of funding sources: None.